Reciprocating Wear Behaviour of Al–SiC Composite Processed with MWS - Bhoi N.K.; Singh H.; Pratap S. (My University, 2025)
The present study involves the fabrication and characterization of Al–SiC composites by means of varying content of SiC (i.e., 5, 10, 15 and 20 wt. %). The material was synthesized with developed hybrid microwave sintering (MWS) technique incorporating powder metallurgy (PM) process. Findings are in good agreement for the selection of reinforcement content in the matrix material for the material development to be used in a lightweight material with improved properties. A systematic approach was made to validate the importance of reinforcement in the matrix material for enhanced product response for various functional applications. The hardness of the developed composite material increases significantly with maximum up to 38.1% for 20 wt.% reinforcement in aluminum. The higher reinforcement percentage in the composite material reduces the wear loss up to 96% as observed in the Al + 20% wt.% SiC composites. © 2022, Springer Nature Singapore Pte Ltd.